A Grey Relation Analysis Method to Vibration Fault Diagnosis of Hydroelectric Generating Set - Wang Ruilian; Gao Shengjian (Institute of Advanced Engineering and Science, 2014)
Aiming to the complexity of vibration fault cause, the great many of fault parameters in hydroelectric generating set, and the superiority of grey relation analysis for its no strict requirement to fault sample capacity and regularity, the weighted grey relation model is built to look for the vibration fault type. The fuzzy matrix's transformation arithmetic is used to obtain the weight vectors of the grey relation coefficient, thus the weighted coefficient is the weighted grey relation model. The relation coefficient between reference sequence and compare sequence in vibration fault sample is provided by synthetic arithmetic of fuzzy weight to diagnose the vibration fault type. The grey relation coefficient weighted by fuzzy synthetic arithmetic, which is not only made the established weight be a scientific basis, but also can “sensitive” highlight the vibration fault type of hydroelectric generating set. Thus the problem of looking for every fault types is better resolved. By analyzing the practical example, it proved that the weighted grey relation model in the paper can effectively diagnose the vibration fault type of hydroelectric generating set and it has definite applicability.